Validity and Reliability of the Spanish Version of Caregiver Abuse Screen (CASE). (January 2015) - Pérez-Rojo, Gema; Nuevo, Roberto; Sancho, Mayte; Penhale, Bridget
Detection of elder abuse risk is a critical issue because a lot of cases remain hidden. Screening tools can be used to detect elder abuse. However, few tools have been developed for use with caregivers. The purpose was to develop a translation and adaptation of a Spanish version of the Caregiver Abuse Screen (CASE) and to assess its validity and reliability. The CASE was then used with 211 primary caregivers. Validity and reliability were evaluated, as well as the factorial structure of the instrument. This version showed good psychometric properties. It was found to have strong internal consistency and split-half reliability as well as allowing for a good replication of the original factorial structure. Additionally, several variables related to elder abuse were linked to the CASE such as depression, burden, frequency, and reactions to problem behaviors. The version developed showed sufficient validity and reliability and could be considered as a suitable instrument to assess risks of elder abuse in a Spanish-speaking context.